Identification of Potential Prognostic Biomarkers Associated With Cancerometastasis in Skin Cutaneous Melanoma - Li, Yang; Lyu, Shanshan; Gao, Zhe; Zha, Weifeng; Wang, Ping; Shan, Yunyun; He, Jianzhong; Huang, Suyang (Frontiers in Genetics, 2021)
Skin cutaneous melanoma (SKCM) is a high aggressive tumor. The mortality and drug resistance among it are high. Thus, explore predictive biomarkers for prognosis has become a priority. We aimed to find the immune cell-based biomarkers for survival prediction. Here, 321 genes were differentially expressed in immune-related groups after ESTIMATE analysis and differential analysis. 219 out of them were associated with the metastasis of SKCM via WGCNA. 26 genes were hub genes in this module. Twelve of them were associated with overall survival (OS) in SKCM patients. After multivariable cox regression analysis, we obtained six of these genes (PLA2G2D, IKZF3, MS4A1, ZC3H12D, FCRL3, P2RY10) were independent prognostic signatures and the survival model of them performed a good prognostic efficacy. The results revealed several key genes that may act as significant prognostic factors of SKCM, which could deepen our understanding of the metastatic mechanisms and improve the treatment of this cancer.